2020
DOI: 10.1111/cas.14340
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab monotherapy in Japanese patients with advanced ovarian cancer: Subgroup analysis from the KEYNOTE‐100

Abstract: Interim results from the two-cohort, phase 2 KEYNOTE-100 study (NCT02674061) of 376 patients with previously treated advanced recurrent ovarian cancer (ROC) showed that pembrolizumab monotherapy was associated with an objective response rate (ORR) of 8.0% (95% CI, 5.4-11.2). We present outcomes for the Japanese patients (n = 21) enrolled in KEYNOTE-100. Patients with epithelial ROC had received either 1-3 prior chemotherapy lines and had platinum-free interval or treatment-free interval (PFI; TFI) of 3-12 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 40 publications
1
21
1
Order By: Relevance
“…Currently, emerging data have reported that ICB immunotherapy could be hopeful for OC patients with recurrence (49). A variety of previously published literatures have reported that OC patients who met the following criteria could probably benefit more from immunotherapy using anti-PD-1/PD-L1 antibodies: (i) highly expressed in PD-L1, (ii) high microsatellite instability (MSI-H), (iii) defective mismatch DNA repair (dMMR), (iv) high tumorinfiltrating lymphocytes with high TMB, and (v) T-cell inflammatory gene expression profile (GEP) (50)(51)(52). Disappointingly, the overall response rate of immunotherapy was still unsatisfactory since the TME of OC was generally in a state of immunosuppression (22).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, emerging data have reported that ICB immunotherapy could be hopeful for OC patients with recurrence (49). A variety of previously published literatures have reported that OC patients who met the following criteria could probably benefit more from immunotherapy using anti-PD-1/PD-L1 antibodies: (i) highly expressed in PD-L1, (ii) high microsatellite instability (MSI-H), (iii) defective mismatch DNA repair (dMMR), (iv) high tumorinfiltrating lymphocytes with high TMB, and (v) T-cell inflammatory gene expression profile (GEP) (50)(51)(52). Disappointingly, the overall response rate of immunotherapy was still unsatisfactory since the TME of OC was generally in a state of immunosuppression (22).…”
Section: Discussionmentioning
confidence: 99%
“…However, a subgroup of these patients with tumours positive for PD-L1, CD8+ infiltrates or both exhibited a significant survival benefit with combination treatment [ 41 ]. Pembrolizumab monotherapy for advanced OC also resulted in a greater ORR in patients with PD-L1 expression, identifying a subpopulation for future ICB OC studies [ 43 ].…”
Section: Immunoregulatory Pathways Within the Tmementioning
confidence: 99%
“…Her unexpected excellent response supports the need to identify other theranostic biomarkers for checkpoint inhibitors [ 1 ]. Because OCCC is prevalent in Asia [ 7 ], a subgroup analysis of 21 Japanese patients with OCCC in the KEYNOTE-100 trial revealed a better objective response rate of these patients (19.0, 95% CI: 5.4–41.9). The hypothesis and the reasons why OCCC showed a better response to immune checkpoint inhibitors require further investigation.…”
Section: Resultsmentioning
confidence: 99%